Loop-mediated isothermal amplification assays: Rapid and efficient diagnostics for genetically modified crops. (December 2019) - Singh, Monika; Pal, Deepa; Sood, Payal; Randhawa, Gurinderjit
Abstract: With the increase in number of globally approved genetically modified (GM) events and diversification of traits, efficient GM detection strategies may play key role for regulatory compliance. Polymerase chain reaction (PCR) and real-time PCR, targeting different components of a transgenic construct, are widely applied analytical methods for GM detection. Loop-mediated isothermal amplification (LAMP), an isothermal nucleic acid amplification method, has been employed in screening and detection of genetically modified organisms (GMOs) since past decade due to user-friendly operation, acceptable specificity, less sensitivity to inhibitors and rapid mode of detection. This article reviews the scenario of applicability of LAMP in GM detection and potential of LAMP. Amplification of LAMP products is done at a constant temperature and no separate steps of denaturation, annealing and extension are required. Easy-to-use portable instrumentation has made this technology applicable for on-site GMO testing. A series of visual and real-time LAMP assays have been developed in recent past for rapid, cost-efficient or on-site detection of GMOs without the involvement of time-consuming electrophoretic analysis. Different chemistries and detection systems can be used on the basis of practical requirement. Amplification can be detected within 30–60 min with a limit of detection (LOD) up to 0.005–0.1% GM content depending on the target or detection system used. Potential of LAMP for further expanding the practical use by modifications/advancement in this technique has also been highlighted in this review. Highlights: Role of loop-mediated isothermal amplification (LAMP) in GM detection is reviewed. Different chemistries and detection systems can be employed for practical use. These assays are user-friendly with acceptable specificity and sensitivity. LAMP facilitates on-site GM detection if combined with fast DNA extraction method. Potential of LAMP for further expanding the practical scope is highlighted.